Earthquake Hazard Analysis in Ciletuh Pelabuhan Ratu Geopark Area, West Java - Ferdian Budi Ar-rouf; Ferryati Masitoh (Universitas Negeri Gorontalo, 2023)
Indonesia is situated between Asia and Australia, as well as the Indian and Pacific Oceans. This circumstance places Indonesia in a geologically complicated pattern, which increases the intensity of earthquakes, tsunamis, volcanoes, and landslides. UNESCO has classified Pelabuhanratu Ciletuh Geopark as a world heritage area. This has resulted in an explosion in tourist and development activity. Even though this tourism destination has the potential for high seismicity, there has been no analysis of the seismic hazard in this region. This study aims to map the earthquake hazard in the Ciletuh Pelabuhan Ratu Geopark Area. This will be important for determining vital assets' placement and development planning. This study employs remote sensing studies and geographic information systems to examine and classify earthquake-prone locations. We evaluated data from DEM, RBI, and soil-type maps. This method evaluates each earthquake hazard metric using the Analytical Hierarchy Process (AHP). The large research area has a slope between 0-300. Few locations have steep slopes. In the Districts of Cisolok, Cikakak, and portions of Pelabuhan Ratu, the characteristics of the huge hard rock are derived from the Quaternary volcanic deposits of Mount Endut. As a result, this region possesses a solid rock structure that can absorb an earthquake propagation wave. This dynamic process of geomorphological creation can also demonstrate that the region surrounding the lineage will feel the effects of a future earthquake. The results show that Ciemas, Simpenan, parts of Cisolok, and Pelabuhanratu districts are included in the moderate to high category of earthquake threats.